Cutaneous manifestations following COVID‐19 vaccination: A report of 25 cases. Issue 8 (4th July 2022) - Shakoei, Safoura; Kalantari, Yasamin; Nasimi, Maryam; Tootoonchi, Nasim; Ansari, Mahshid Sadat; Razavi, Zahra; Etesami, Ifa
Abstract: Various adverse effects particularly cutaneous manifestations associated with different COVID‐19 vaccines have been observed in practice. The aim of our study was to evaluate all patients who presented to our tertiary center with skin manifestations following COVID‐19 vaccines injection from September to December 2021. All patients with skin manifestation within 30 days or less following COVID‐19 vaccination were enrolled in our case‐series. All cases included in our study were diagnosed based on clinical and/or histopathological evaluation and all other possible differential diagnoses were ruled out. Twenty‐five individuals including 16 (64%) males and 9 (36%) females with the mean age of 47 ± 17.62 years (range 18–91) were enrolled in our study. Twenty‐two (88%) patients developed lesions after Sinopharm vaccine injection and 3 (12%) cases manifested lesions after the AstraZeneca vaccine. Six (24%) patients developed new‐onset lichen planus (LP) and 1 (4%) patient manifested LP flare‐up. Two (8%) individuals developed psoriasis and 1 (4%) case showed psoriasis exacerbation. One (4%) patient developed new‐onset pemphigus vulgaris (PV) and 1 (4%) case experienced a flare of PV lesions. One (4%) patient manifested pityriasis lichenoides et varioliformis acuta (PLEVA) flare‐up. Other new‐onset cases were as follows: toxic epidermal necrolysis (TEN) (n = 1, 4%), bullous pemphigoid (BP) (n = 2, 8%), alopecia areata (AA) (n = 2, 8%), pytriasis rosea (n = 1, 4%), herpes zoster (n = 1, 4%), cutaneous small vessel vasculitis (n = 1, 4%), erythema multiform (EM) and urticaria (n = 3, 12%), and morphea (n = 1, 4%). Physicians should be aware of the possible side effects especially cutaneous manifestations associated with COVID‐19 vaccines.